“Physiological and demographic responses of Nilaparvata lugens to combined climate stressors: CO2, temperature, and ozone” - Yele, Yogesh; Chander, Subhash; Suroshe, Sachin S.; Tenguri, Prabhulinga; Sundaran, Arya Pattathanam; Pandi, G. Guru Pirasanna; Bhatia, Arti; Patel, Chenesh (Frontiers in Plant Science, 2025)
Climate change factors, including elevated carbon dioxide (eCO2), elevated ozone (e03), and the combined effect of elevated temperature and CO2 (eT+eCO2), significantly influence the population dynamics, development, and feeding behavior of the Brown Planthopper (Nilaparvata lugens, BPH) and its impact on rice yield. A two-year field study (2019–2020) showed that BPH populations were highest under eCO2 (61.6 ± 13.5 and 50.6 ± 12.3 N. lugens/hill) and moderate under eT+eCO2 (44.5 ± 9.4 and 47.5 ± 12.1 N. lugens/hill), while e03 drastically reduced populations (17.7 ± 3.1 and 25.1 ± 7.0 N. lugens/hill). Fecundity followed a similar trend, with the highest egg production under eCO2 (219.7 ± 3.3 and 234.3 ± 9.7 eggs/female), moderate under eT+eCO2 (194.2 ± 6.3 and 223.5 ± 9.2 eggs/female), and lowest under e03 (108.4 ± 6.0 and 135.6 ± 3.7 eggs/female). Developmental duration was shortest under eT+eCO2 (14.9 ± 0.3 and 15.9 ± 0.4 days) and longest under e03 (18.2 ± 0.40 and 21.7 ± 0.40 days). Feeding intensity, indicated by honeydew excretion, was highest under eCO2 (124.8 ± 5.3 and 131.3 ± 4.2 mm²), reduced under eT+eCO2 (105.7 ± 4.9 and 107.6 ± 3.4 mm²), and lowest under e03 (44.2 ± 2.5 and 48.9 ± 2.6 mm²). Results indicated that eCO2 promoted overall plant growth, with the highest plant height (65.4 ± 0.8 cm) and reproductive tillers (22.2 ± 0.6). However, under BPH infestation, eCO2 also resulted in the highest yield reduction (15.9%) despite producing the highest grain yield under uninfested conditions (40.1 ± 0.3 g/hill). The eT+eCO2 treatment exhibited moderate reductions in plant height (62.4 ± 0.6 cm) and grain yield (38.1 ± 0.4 g/hill), with a yield loss of 11.5% under infestation. The e03 treatment negatively impacted plant growth, significantly reducing plant height (54.8 ± 1.0 cm), total tillers (17.7 ± 0.9), and grain yield (27.5 ± 0.2 g/hill) in uninfested conditions, with a lower yield reduction (8.72%) under infestation. The findings of this study indicate that pests and host plants benefited under eCO2 and eT+eCO2 conditions; however, increasing BPH populations caused yield losses. Nevertheless, e03 had a detrimental effect on pests as well as host plants. The results pertaining to the collective impact of climate change factors on both the host plant and pests have the potential to contribute to the advancement of insect pest management strategies in response to shifting climates.